EFFECT OF NETTLE ON PRODUCTIVE PERFORMANCE OF BROILERS AND ITS BIOCHEMICAL, HISTOLOGICAL, IMMUNOLOGICAL, AND ANTIOXIDANT CHARACTERISTICS - Nareen Sadeeq; shawkat M'Sadeq; Sleman Beski (Mesopotamia Journal of Agriculture)
This study was carried out to evaluate the impact of adding nettle plant to the food on the physiological and productive performance of broiler chickens. Three dietary levels (0, 1.5 and 3 g/kg) of either fermented or non-fermented nettle powder were added to broiler diets. Up to 10 days body weight and weight gain were not significantly elevated. However, the interaction of the experimental factors improved FCR (P<0.05). The interplay of experimental conditions resulted in a rise in FI in the nettle-supplemented groups during the 35-day trial period. Feed intake, body weight and weight gain increased (P<0.05) when the supplementary level of nettle increased in broiler diets. Serum lipid profile of broilers improved by nettle supplementation. Jejunum villi length and intestinal absorptive area were increased with the amount of nettle in broiler meals. Nettle fermentation significantly increased the intestinal absorptive area of broilers. The interaction of experimental factors increased the NDV and IB titers and the total antioxidant capacity (TAC) in the serum of nettle-supplemented birds. The NDV and IB titers were decreased by nettle fermentation; however, the NDV and IB titers and TAC were increased when the supplementary level of nettle increased. The activity of glutathione peroxidase (GPX), catalase, and SOD increased in nettle-supplemented broilers. Nettle supplementary level and fermentation significantly increased the GPX in broilers. The level and fermentation of nettle increased the catalase activity in the broilers. Nettle fermentation significantly increased the activity of SOD in the broiler chickens.